TECHNICAL AND ECONOMIC ASSESSMENT OF MARITIME ACCIDENTS (International Journal of Scientific Research and Management (IJSRM), 2022)
This article highlights the main technical and statistical aspects related to maritime accidents, including the various types of vessels that navigate rivers and oceans around the world. It seeks to understand the mechanics of different accidents, their recurrence for different causes and their financial impact. Technically, through case studies, it shows the different types of accidents that occur in different global locations. The preservation of human life as well as of the environment are determining factors in any maritime accident today. Keywords: Maritime Casualties, Class Society, International Maritime Organization, Environment, Costs, Cases